PERANCANGAN APLIKASI SISTEM PEMESANAN RUANG RAPAT PADA MCD INDONESIA BERBASIS JAVA DAN MYSQL - Tria Hadi Kusmanto; cahyo, alqomari; Zulfitri Maulana Rinaldi (Lembaga Pengembangan Kinerja Dosen, 2022)
The business growth of large companies requires the support of office infrastructure to help the organization's activities. One of them happened in the management of the meeting room at PT. National Food Rekso is manually using Microsoft Outlook to find out and manage the availability of meeting rooms and reservations by the secretaries of each department. This process is very ineffective because checking and confirming space availability takes a relatively long time. With the limited number of meeting rooms and the high level of need for meeting rooms, meeting room management requires practical and appropriate application support.